The significance of low‐level viraemia in diverse settings: analysis of the Treat Asia HIV Observational Database (TAHOD) and the Australian HIV Observational Database (AHOD). Issue 7 (26th January 2014) - Kanapathipillai, R; McManus, H; Cuong, DD; Ng, OT; Kinh, NV; Giles, M; Read, T; Woolley, I
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to assess the significance of low‐level viraemia (LLV) and the timing of treatment change in low/middle‐income country (L/MIC) compared with high‐income country (HIC) settings. Methods Patients with virological control following commencement of combination antiretroviral therapy (cART) were included in the study. LLV was defined as undetectable viral load (<50 HIV‐1 RNA copies/mL) followed by confirmed detectable viral load < 1000 copies/mL. Virological failure was defined as viral load > 1000 copies/mL. Kaplan−Meier plots of time to virological failure by prior LLV and income category were generated. Regimen changes in the setting of LLV were compared between sites. Sensitivity analysis of rates of LLV and virological failure by person‐years and number of tests was conducted for differing definitions of LLV and virological failure. Results A total of 1748 patients from HICs and 823 patients from L/MICs were included in the study. One hundred and ninety‐six (11.2%) HIC participants and 36 (4.4%) L/MIC participants experienced at least one episode of LLV. Of the patients who underwent regimen switch in HIC settings, the majority changed from a nucleoside reverse transcriptase inhibitor (NRTI)/protease inhibitor (PI) regimen to an NRTI/nonnucleoside reverse transcriptase inhibitor (NNRTI) regimen (26.8%). Very few switches were made in L/MIC settings. Rates of LLV were significantly higher for HICs compared with L/MICs per 1000 person‐years (28.6 and 9.9 per 1000 person‐years, respectively), but not in terms of the number of tests (9.4 and 7.2 per 1000 tests, respectively). Rates of virological failure per test were significantly higher for L/MICs compared with HICs (30.7 vs. 19.6 per 1000 tests, respectively; P < 0.001). LLV was a significant predictor of virological failure at 2 years in L/MICs [0.25; 95% confidence interval (CI) 0.11–0.50; P = 0.043] but not in HICs (0.13; 95% CI 0.08‐0.22; P = 0.523). Conclusions LLV is weakly predictive of virological failure at 2 years in L/MICs but not in HICs. This suggests that interventions targeted at subjects with LLV in L/MICs would help to improve treatment outcomes.